1998
DOI: 10.1046/j.1523-1755.1998.00099.x
|View full text |Cite
|
Sign up to set email alerts
|

The multidimensional nature of renal disease: Rates and associations of albuminuria in an Australian Aboriginal community

Abstract: Renal disease in this population is multifactorial, with risk factors related to whole-of-life nutrition, metabolic and hemodynamic profiles, infections, health behaviors, and possibly a family predisposition. Its relationship to low birth weight, and its associations with deteriorating metabolic and hemodynamic profiles, suggest that renal disease is, in part, a component of Syndrome X, which explains the simultaneous increase in metabolic, cardiovascular and renal disease in Aboriginal people. The family clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
171
1
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 191 publications
(186 citation statements)
references
References 37 publications
13
171
1
1
Order By: Relevance
“…24 Given albuminuria is a marker of early chronic kidney disease, this suggests that APSGN may be contributing to the extremely high rates of chronic renal failure seen in Indigenous Australian adults. 25 The incidence rates in this study included only notified confirmed cases. Case ascertainment and reporting is likely to be incomplete.…”
Section: Discussionmentioning
confidence: 99%
“…24 Given albuminuria is a marker of early chronic kidney disease, this suggests that APSGN may be contributing to the extremely high rates of chronic renal failure seen in Indigenous Australian adults. 25 The incidence rates in this study included only notified confirmed cases. Case ascertainment and reporting is likely to be incomplete.…”
Section: Discussionmentioning
confidence: 99%
“…15,71,[113][114][115][116][117] The earliest evidence from Australian Aboriginals found an odds ratio of 2.8 for macroalbuminuria in those who had been of LBW compared with NBW. 15,71,113,114 In addition, the degree of albuminuria predicted loss of renal function and strongly correlated with mortality. 71,72 Similarly, among Pima Indians with type 2 diabetes, the prevalence of albuminuria was higher in those who had birth weights Ͻ2500 or Ͼ4500 g compared with those of NBW.…”
Section: Proteinuriamentioning
confidence: 99%
“…Diabetes and hypertension strongly predict the presence of albuminuria in several population studies [10±14]. Some studies have indicated that abdominal obesity, insulin resistance and dyslipidaemia are also independently associated with albuminuria [2,11,14].…”
mentioning
confidence: 99%